Anaktuvuk Pass goes to town - Blackman, Margaret (Études/Inuit/Studies)

(untitled) (Association Inuksiutiit Katimajiit Inc., 2008)
AbstractThe Nunamiut of Anaktuvuk Pass, Alaska have been going to town, one way or another, even before they relinquished their nomadic life in 1949-1950 to become settled in a village 100 miles from the nearest road and 250 miles from Fairbanks. Some years before they ever set foot in town, a few had credit accounts at the city’s Northern Commercial Company. In the mid-1950s a few village men were recruited as human subjects for cold adaptation experiments carried out at Ladd AFB outside of Fairbanks. This was their first plane ride and their first taste of city life. Medical emergencies—a flu epidemic, TB, and other illnesses that demanded medical treatment were the other ticket to Fairbanks in the 1950s, and then one typically had to wait to be flown out until the monthly mail plane came in. But by the 1960s the Native health care system saw to it that Anaktuvuk women came to town to deliver their babies in the hospital. Today Fairbanks is not only the doctor’s office but also the shopping mall and supermarket for outlying villages like Anaktuvuk Pass. It is many other things as well to the Nunamiut—site of the annual World Eskimo-Indian Olympics, the University of Alaska’s annual Festival of Native Arts, and the summer Tanana Valley Fair. It is Second Avenue with its string of dingy bars. This paper looks at more than 50 years of going to town, the significance of “town” in villagers’ lives, and the varied associations Fairbanks holds for the Nunamiut.